Predictors of Hospitalization Among Older Adults with COVID-19 in Saudi Arabia: A Cross-Sectional Study of a Nationally Representative Sample - Alamri F; Alsofayan Y; AlRuthia Y; Alahmari A; Almuzaini Y; Abo Gazalah F; Alradini F; Alaama T; Khan A (Dove Medical Press, 2021)
Fahad Alamri,1,* Yousef Alsofayan,1 Yazed AlRuthia,2,3,* Ahmed Alahmari,1 Yasir Almuzaini,1 Fouad Abo Gazalah,4 Faten Alradini,5 Tareef Alaama,6 Anas Khan1,7 1Global Center for Mass Gatherings Medicine, Ministry of Health, Riyadh, Saudi Arabia; 2Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 3Pharmacoeconomics Research Unit, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 4General Director of Health Centers Affairs, Ministry of Health, Riyadh, Saudi Arabia; 5Department of Family Medicine, Faculty of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 6Deputyship of Therapeutic Services, Ministry of Health, Riyadh, Saudi Arabia; 7Department of Emergency Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia*These authors contributed equally to this workCorrespondence: Yazed AlRuthia Tel +996 114677483Fax +966 114677480Email yazeed@ksu.edu.saFahad Alamri Email faabalamri@moh.gov.saBackground: The aim of this study was to identify the predictors of hospitalization in older (≥ 60 years) patients with coronavirus disease-19 (COVID-19) in Saudi Arabia.Methods: Patients were randomly selected from a COVID-19 database maintained by the Ministry of Health, Saudi Arabia. All patients were aged ≥ 60 years, had reverse transcriptase-polymerase chain reaction (RT-PCR)-confirmed COVID-19, and were registered in the database during March 2020 to July 2020. Medical and sociodemographic characteristics were retrieved from the database. Additional data were collected by telephone interviews conducted by trained health professionals. Descriptive statistics and multiple logistic regression analyses were used to analyze the relationship between patient characteristics and the risk of hospitalization.Results: Of the 613 included patients (51.1% females), more than half (57.3%) were between 60 to 69 years of age, and 53% (324/613) had been hospitalized. The independent predictors of hospitalization included age ≥ 65 years (OR = 2.35, 95% CI: 1.66– 3.33, P < 0.001), having more than one comorbidity (OR = 1.55, 95% CI: 1.09– 2.20, P = 0.01), diabetes mellitus (OR = 1.52, 95% CI: 1.09– 2.11, P = 0.01), hypertension (OR = 1.40, 95% CI: 1.007– 1.97, P = 0.04), chronic kidney disease (OR = 3.87, 95% CI: 1.41– 10.58, P = 0.008), and history of hospital admission within the preceding year (OR = 1.69, 95% CI: 1.11– 2.55, P = 0.013). Risk of hospitalization was lower in males (OR = 0.65, 95% CI: 0.43– 0.90, P = 0.01) and in patients co-living with health care workers (OR = 0.64, 95% CI: 0.43– 0.96, P = 0.03).Conclusion: Factors associated with higher risk of COVID-19-associated hospitalization should be used in prioritizing older adults’ admission. Future studies with more robust designs should be conducted to examine the risk of COVID-19-associated illness severity and mortality.Keywords: COVID-19, older adults, hospitalization, diabetes, hypertension, chronic kidney disease, Saudi Arabia